2015
DOI: 10.1177/0741932515575614
|View full text |Cite
|
Sign up to set email alerts
|

Response Cards as a Strategy for Increasing Opportunities to Respond

Abstract: This study evaluated the quality of the research and evidence base for using response cards to increase opportunities to respond (OTR) for students with and without disabilities at the elementary level (i.e., kindergarten through Grade 5). Using quality indicator criteria for single-case research, six single-case studies investigating response cards were analyzed.Based on an analysis of quality indicators, results established the use of response cards as an evidence-based practice with a moderate level of evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Overall, results from this EBP review are similar to Schnorr et al's (2015) review in which the authors found sufficient support for response cards as an EBP. We extended their work and found a range of research examining OTR strategies (e.g., response cards, choral responding) to be methodologically rigorous and effective.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Overall, results from this EBP review are similar to Schnorr et al's (2015) review in which the authors found sufficient support for response cards as an EBP. We extended their work and found a range of research examining OTR strategies (e.g., response cards, choral responding) to be methodologically rigorous and effective.…”
Section: Discussionsupporting
confidence: 73%
“…Findings suggested choral responding resulted in higher levels of active student responding and on-task, appropriate behavior, as well as decreases in students' disruptive and inappropriate behaviors. More recently, Schnorr et al (2015) offered the first methodological appraisal of an OTR strategy and examined response cards in elementary settings. Results indicated sufficient support for response cards as an EBP with a moderate level of evidence for increasing OTR for elementary students.…”
Section: Opportunities To Respond: Lessons Learnedmentioning
confidence: 99%
“…Effective behavior specific praise (BSP) was defined as contingent verbal statements of approval provided to a student, or students, by a paraeducator that includes a reference to or a description of the behavior being praised (Hawkins & Heflin, 2011). Effective opportunities to respond (OTR) was defined as an interaction between a paraeducator formulated question and the academic response given by the student or students (Schnor, Freeman-Green, & Test, 2015). Specifically, effective OTR was described as a questioning technique that served to begin, review, or extend a learning trial.…”
Section: Methodsmentioning
confidence: 99%
“…OTR are created within a teacher-directed instructional plan (i.e., materials, questioning, prompts) that produces active participation by providing students with routes to generate answers or respond to instruction in the classroom (Cappizzi, Wehby, & Sandmel, 2010; Greenwood, Delquadri, & Hall, 1984). OTR can increase engagement, academic outcomes, and reduce problem behaviors (Schnorr, Freeman-Green, & Test, 2015). Evidence indicates that increased levels of teacher-directed OTRs for students with EBD yield positive effects on academic and behavioral outcomes, including increased engagement (MacSuga-Gage & Simonsen, 2015; Sutherland & Wehby, 2001).…”
Section: Behaviors Of Students With Ebd That Influence Academic Perfomentioning
confidence: 99%
“…Current research illustrates that response cards (e.g., white tile boards, premade cards, electronic responders) can be an effective method for increasing active participation for students with and without disabilities over the broad range of ages and development (Horn, 2010; Randolph, 2007; Schnorr et al, 2015). Several studies have investigated middle school students, self-contained settings, and/or math achievement (Berrong, Schuster, Morse, & Collins, 2007; Davis & O’Neill, 2004; Horn, Schuster, & Collins, 2006; Lambert, Cartledge, Heward, & Lo, 2006; Maheady, Michielli-Pendl, Mallette, & Harper, 2002).…”
Section: Response Cards As An Instructional Toolmentioning
confidence: 99%